Review Of Cream Of The Criminological Physical Violence Against Children (Study On The Verdict Number 47/Pid.sus/2021/PN.Jkt.Pst) - Sifani, Putri; Purwaningsih, Prihatini; Lestari, Nisa (Universitas Ibn Khaldun Bogor, 2023)
In the Indonesian human rights are really very prioritized, including the rights of the child, today a lot of violence that occurs against children undertaken by some parents, which is neglected. The purpose of this study is to know the factors that cause physical violence against children and the application of sanctions to the perpetrators at the decision of the number 47 / Pid.sus / 2021 / PN.Jkt.Pst. The method used in this research descriptive analysis (describes the researched), with normative juridical approaches, data sources using secondary data obtained through literature studies, data collection techniques by the library study analyzing the case is made by the judge's verdict, legal journals, and legal books, associated with the case of physical violence against children. and qualitative analysis techniques. The results of this study, first, the factor that causes the physical violence against children is derived from the mother who is neglected, in providing a good, lower pattern, too letting children to fall over and over, the lack of attention from the mother to children when children have a history of disease, and lack of mother's understanding of children in educating to follow their commands so every child makes the mistake of violence that occurred. Second, the application of criminal sanctions to the perpetrators in the verdict of number 47 / Pid.sus / 2021 / PN.Jkt.Pst. It has been in accordance with the laws and regulations in this regarded regarded in Article 76C Jo 80 Paragraph (3) Law RI no. 35/2014 on changes to Law no. 23/2002 on child protection.